MATERIAL REFLETOR PRATEADO E COLORIDO NO CRESCIMENTO DE BARU (DIPTERYX ALATA VOG.) EM AMBIENTES PROTEGIDOS - VEIGA, Enitieli Pereira; COSTA, Edilson; FERREIRA, Amanda Maria Frata; VETRUVE, Italo Ferreira; ROCHA, Alana Silva (ANAIS DO ENIC, 2024)
-